1990
DOI: 10.1002/neu.480210102
|View full text |Cite
|
Sign up to set email alerts
|

Competitive mechanisms underlying synapse elimination in the lumbrical muscle of the rat

Abstract: The process of neuromuscular synapse elimination has been studied in the fourth deep lumbrical (4DL) muscle of the rat, a preparation which offers technical advantages for some types of experimental work. Studies have been performed both during development and in adult denervated muscles undergoing reinnervation. Results indicate that synapse elimination is dependent upon competition between motoneurons. Cellular mechanisms underlying this competition have also been explored. Both neuromuscular activity and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Neonatal synapse elimination is a competitive (Betz et al, 1989;Balice-Gordon and Lichtman, 1994) and activity-dependent (O'Brien et al, 1978;Thompson, 1985;Busetto et al, 2000) process by which all but one of the multiple nerve terminals are eliminated from the NMJ (for review, see Sanes and Lichtman, 1999). We found that synapse elimination was significantly delayed in the NCAM null semitendinosus muscle, as also observed for the sternomastoid muscle (Moscoso et al, 1998).…”
Section: Neonatal Synapse Elimination Is Delayed In Ncam Null Junctionssupporting
confidence: 53%
“…Neonatal synapse elimination is a competitive (Betz et al, 1989;Balice-Gordon and Lichtman, 1994) and activity-dependent (O'Brien et al, 1978;Thompson, 1985;Busetto et al, 2000) process by which all but one of the multiple nerve terminals are eliminated from the NMJ (for review, see Sanes and Lichtman, 1999). We found that synapse elimination was significantly delayed in the NCAM null semitendinosus muscle, as also observed for the sternomastoid muscle (Moscoso et al, 1998).…”
Section: Neonatal Synapse Elimination Is Delayed In Ncam Null Junctionssupporting
confidence: 53%
“…This question emerges out of a CNTF Regulates Synapse Elimination DevNeurosci 1996;18:185-198 long-held belief that synapse elimination is a competitive process, i.e., synapses compete for a trophic substance that is supplied by the target cells in limited amounts [recent reviews : Betz et al, 1990;Lichtman and BaliceGordon, 1990;Herrera and Werle. 1990;Van Essen et al, 1990;Colman and Lichtman, 1993].…”
Section: Discussionmentioning
confidence: 99%
“…The idea that the survival of developing motoneurons and their synapses depends on competition for targetderived trophic factors is both pervasive and long stand ing [recent reviews : Purves, 1988;Purves et al, 1988;Betz et al, 1990;Lichtman and Balice-Gordon, 1990;Herrera and Werle, 1990;Barde, 1989;Oppenheim, 1991;Thoenen et al. 1993;Colman and Lichtman, 1993;Ip and Yancopoulos, 1994], Hamburger [1934Hamburger [ , 1939 provided an early hint that developing motoneu rons might compete for target-derived trophic factors by demonstrating that the number of surviving motoneurons is a function of target size.…”
mentioning
confidence: 99%
“…The nerve terminal and postsynaptic structure expand and AChRs become metabolically stable. The final stage involves the postnatal maturation of the neuromuscular junction and includes numerous changes on both a cellular and a molecular level: AChR subunits and channel kinetics change (Sakmann and Brenner, 1978;Mishina et al, 1986;Gu and Hall, 1988), synaptic vesicle proteins are restricted to the nerve terminal (Lupa and Hall, 1989;Dahm and Landmesser, 1991) subsynaptic folds appear (Terivainen, 1968;Kelly and Zacks, 1969) and polyneuronal innervation is eliminated (Betz et al, 1990).…”
mentioning
confidence: 99%